The Impact of Natural Suckling on Milk Yield and Growth Rates of Kids of Nubian Goats - A . H, EL Said; Abu Nikhaila A. M, Abu Nikhaila; Khalid, A.M.; University of Khartoum, A.E.1 (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to evaluate the effect of suckling on milk production of Nubian goats and growth rates of respective kids. The study involved 20 multiparous Nubian goats allocated randomly according to body weight and age to two equal groups of 10 does each. Group A suckled their kids for 13 weeks, while group B (control) was not suckled and their kids were reared artificially by bottle for 13 weeks. The results indicated a significant (P< 0.05) difference for the daily milk yield (kg) in favour of the suckled group. The recorded values were 1.07±0.3 versus 0.8±0.28 (kg day) for group A and B, respectively. The peak yield in group A and B was 1.5±1.1 and 1.2±0.1 (kg), respectively. The present study revealed significant (P<0.01) differences of the total milk yield per lactation with values of 180.7±45.4 compared to 110.2±65.3 (kg lactation) for the two groups, respectively. The lactation length was significantly (P<0.05) longer in group A than that in group B with values of 174.6±46.7 and 128.6 ±36.9 days, respectively. Kids milk consumption and conversion efficiency in the two groups were in significant (P>0.05) as indicated by the similar growth rate in the two groups. The sex of kid, however had exerted a significant effect on growth rate during the second and third week of age, whereby the male kids had a highly significant (P<0.05) growth rate than female mates.